Clinical Overview of Extrapulmonary Small Cell Carcinoma - Kim, Kyeong-Ok; Lee, Ha-Young; Chun, Sung-Ho; Shin, Sang-Joon; Kim, Min-Kyoung; Lee, Kyung-Hee; Hyun, Myung-Soo; Bae, Sung-Hwa; Ryoo, Hun-Mo (Journal of Korean medical science, 2006)
The objective of this study was to review the natural history of extrapulmonary small cell carcinoma (EPSCC) with specific emphasis on clinical features, response to treatment and survival. The records of all patients (n=34) with EPSCC treated at Yeungnam University Medical Center and Catholic University of Daegu Medical Center between 1998 and 2005 were retrieved and reviewed. The primary sites of tumor were the esophagus and thymus in 6 patients (17.6%) each, pancreas and stomach in 5 patients each (14.7%); other sites included were the cervix, abdominal lymph nodes, abdominal wall, bladder, colon, maxillary sinus, nasal cavity, ovary, parotid gland and liver. Twenty three patients out of 34 had limited disease. The median survival of all patients was 14 months. Independent prognostic factors included stage and primary tumor location. The prognosis for the patients with extensive disease and in the gastrointestinal group was unfavorable. EPSCC is a non homogeneous disease entity. As a result of its frequent recurrence, multimodal therapy has a better outcome even in cases of limited disease. Combination chemotherapy plays a central role for treatment of extensive disease in EPSCC. Further multicenter studies are now needed to determine more details regarding disease sub-class and optimal treatment modality.